The role of the international community - Gunnar M Sørbø (Forced Migration Review, 2005)
The Comprehensive Peace Agreement represents a major opportunity for positive change and sustainable peace in Sudan. History shows, however, that the potential for peace breaking down is great. Continued engagement of the international community could prove crucial.